Tingkat Substitusi Teknikal Marjinal dalam Kombinasi Penggunaan Pupuk pada Usahatani Cabai Merah Besar di Desa Baturiti Kabupaten Tabanan - WIDYANTARA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.1, Januari 2017, 2017)
Marginal Rate of Technical Susbtitution in Combined Use of Fertilizer in LargeRed Chili Farming in Baturiti Village Tabanan Regency Large red chilli farming is intensive farming, so farmers in managing their farmingexperience various problems, both problems in farming and environmental issues.The purpose of this study was to determine: (1) marginal rate of technicalsubstitution (MRTS) from a combination of the type of fertilizers used, (2) the effectof changes of the use of fertilizers on the use of other fertilizers, and (3) theoptimization of allocation combinations of fertilizers in big red chili farming,whether it had qualified for optimal requirements. The results showed that, from acombination of fertilizers (urea, ZA, KCl, TSP, NPK) used by large red chili farmers,only NPK fertilizer which wassubstitutable with ZA fertilizers and urea fertilizerswhile other fertilizers are complementary in nature, MRTS of urea with NPKof0.058, and MTRS ZA with NPK of 0.118. NPK fertilizers were not perfectsubstitutes of the ZA and the urea fertilizers. The substitution abilitywas only 11%against ZA and 13% against urea. From the combination of the use of fertilizers inlarge red chillifarming, none of the combinations was optimal. It is suggestedfarmers should improve their skills in the use of a combination of various types offertilizers in chillifarming, so that costs can be minimized andthe profit of farmingcan be maximized.
Keywords: combination of fertilizer allocation; optimization of the use of fertilizers; large red chilli farming